"Apical sparing" T‐wave inversion in a case of mid‐ventricular takotsubo syndrome. Issue 3 (18th January 2021) - Giannattasio, Alessia; Baritussio, Anna; Gallucci, Marco; Migliore, Federico; Corrado, Domenico; Zorzi, Alessandro
Abstract: Previous studies showed that myocardial edema correlates with dynamic T‐wave inversion and QTc prolongation in a variety of acute cardiovascular diseases including takotsubo syndrome (TTS). We reported the case of a patient with "atypical" (mid‐ventricular) TTS showing a unique pattern of diffuse T‐wave inversion that spared only the apical precordial leads V3–V4. Cardiac magnetic resonance (CMR) showed myocardial edema involving all mid‐ventricular segments but not the apex. Both ECG and CMR normalized at follow‐up evaluation. This case further reinforces the theory of an association between presence and regional distribution of acute myocardial inflammation and dynamic repolarization changes.